The relationship between unsafe acts and the incidence of work accidents in welder workers at PT Lintech Seaside Facility - Al Khiqni Mochammad Aqwam; Sestiono Mindiharto (Jurnal EduHealth, 2024)
Unsafe action is a behavior or action taken by workers in carrying out their work so that these actions can increase the possibility of work accidents if not changed. Unsafe behavior (unsafe action) that still occurs a lot such as not using personal protective equipment (PPE), improper use of personal protective equipment (PPE), less careful or careless, lack of experience and knowledge. This study aims to analyze the relationship of unsafe actions to the incidence of work accidents in welder workers at PT Lintech Seaside Facility. This type of research is quantitative research with a cross sectional approach. This research was conducted by distributing questionnaires. The sample in the study were 38 welder workers at PT Lintech Seaside Facility. The sampling technique is probalility sampling with simple random sampling method. The results of research on welder workers at PT Lintech Seaside Facility who have experienced work accidents and have a high level of unsafe action are 92.3%, while those who have never experienced work accidents and have a high level of unsafe action are 7.7%. The results of the Coefficient Cotigency correlation test show that the p-value = 0.001. The results concluded that there is a significant relationship between unsafe actions and the incidence of work accidents.